Children’s right to play in Chilean hospitals: A forgotten right?—A qualitative study protocol - Aleksandra Głos; Alejandra Santana López; Ivonne Vargas Celis; Lilian Sanhueza Díaz; Constanza Quezada (PLoS ONE, 2025)
Background Despite being a recognised human right (art. 31 of the United Nations Convention on the Rights of the Child), children’s right to play is still insufficiently researched, understood and, above all, implemented. In Chile, the National Child Health Programme recognises the importance of this right for the hospitalised children but makes its provision dependent on the hospital’s capacity. We therefore hypothesise that the provision of children’s right to play in Chilean hospital settings will be irregular, varying from institution to institution, possibly reflecting the existing socio-economic inequalities in the country, thereby leaving much room for improvement. Aims This study aims to collect qualitative data on the institutional arrangements and opportunities for children’s play in public hospitals in Chile. Specifically, our goal is to (a) interpret the conditions and opportunities for play that Chilean public hospitals provide to children and adolescents; (b) interpret institutional arrangements and professional experiences of children’s play in those institutions; (c) identify factors that favour and/or limit opportunities for children’s play in the Chilean hospital setting. Methods This is exploratory qualitative research, combining multiple and instrumental case study with ethnographic research. Its data collection techniques are semi-structured interviews with professionals in hospital settings (supported by a self-assessment questionnaire), and non-participant observations of hospital playrooms (and/or other play spaces). Conclusion This will be the first study to investigate children’s right to play in Chilean hospitals, with a particular focus on the extent of its implementation, its understanding among health professionals, as well as existing limitations and opportunities for its development.